2021
DOI: 10.1186/s13049-021-00842-0
|View full text |Cite
|
Sign up to set email alerts
|

Introducing fairness in Norwegian air ambulance base location planning

Abstract: Background A primary task of the Norwegian helicopter emergency medical services (HEMS) is to provide advanced medical care to the critical ill and injured outside of hospitals. Where HEMS bases are located, directly influences who in the population can be reached within a given response time threshold and who cannot. When studying the locations of bases, the focus is often on efficiency, that is, maximizing the total number of people that can be reached within a given set time. This approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Appropriate resource management seems to be a recurring concern among emergency professionals, since they move in an environment with scarce resources that must be used and positioned in the most effective and efficient way possible. 16 In addition, there are multiple studies that link new technologies, big data, and artificial intelligence (identified as a priority) with the management of calls and the sending of resources by the Emergency Call Center. 17,18 Therefore, there are links between research priorities, which highlights the need for a cross-sectional approach as one of the elements to consider in prehospital emergency research.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate resource management seems to be a recurring concern among emergency professionals, since they move in an environment with scarce resources that must be used and positioned in the most effective and efficient way possible. 16 In addition, there are multiple studies that link new technologies, big data, and artificial intelligence (identified as a priority) with the management of calls and the sending of resources by the Emergency Call Center. 17,18 Therefore, there are links between research priorities, which highlights the need for a cross-sectional approach as one of the elements to consider in prehospital emergency research.…”
Section: Discussionmentioning
confidence: 99%
“…5) Fairness in resource allocation: Resource allocation problems (RAPs) [156] are ubiquitous in many areas, such as task scheduling [157], [158], emergency service allocation [159], [160] and Cloud service allocation [44], [43]. In recent decades, equitable allocation of resources that ensures equitable distribution of resources to users [39], [40], [41], has become a popular research topic.…”
Section: Fairness In Multi-objective Optimizationmentioning
confidence: 99%
“…In [166], the notion of fairness is to ensure that the maximization of the covered demand of one facility does not negatively impact the demand coverage of others. In ambulance location problem [160], [167], the fairness is denoted by the maximization of Bernoulli-Nash social welfare [168], i.e., maximizing the joint probability that everyone receives ambulance on time.…”
Section: Fairness In Multi-objective Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Norway currently has 13 HEMS bases, established through historical local engagement from the late 1970s, with gradual expansion covering an increasing part of Norway [ 15 ]. Several studies have used mathematical models to study the optimal location of HEMS bases in Norway based on minor adjustments to the existing resources [ 3 , 5 , 15 ]. However, what it takes to bring response times in Norway down to times comparable to those on mainland Europe remains unexamined.…”
Section: Introductionmentioning
confidence: 99%